DINAMIKA SENIORITAS DAN PERILAKU BULLYING DI LINGKUNGAN PENDIDIKAN BERBASIS ASRAMA - Jimly Assiddiqi; Miftahuddin; M. Fahli Zatrahadi (Counseling Milenial (CM), 2026)
Bullying in boarding-based educational environments needs attention because students live in close, repeated, and not always well-supervised social spaces. One relational pattern that may influence this condition is seniority. Seniority can help junior students adapt to boarding school rules and culture, but it may also turn into a space of domination when it is not supported by clear boundaries, supervision, and educational values. This article aims to examine the dynamics of seniority and bullying behavior in boarding-based educational environments. This study used a literature review method with a qualitative-descriptive approach. The reviewed literature consisted of national journal articles, official sources, and methodological references relevant to seniority, senior-junior relations, bullying, pesantren, boarding schools, and violence prevention. The findings show that seniority has educational value when practiced through role modeling, mentoring, responsibility, and supervision. Conversely, seniority accompanied by pressure, humiliation, domination, and normalized violence can encourage verbal, physical, social, and psychological bullying. Prevention should be directed through reorganizing senior roles, assisting junior students, strengthening caretaker supervision, developing continuous anti-bullying education, and providing safe reporting mechanisms.